Collisionality scaling of the electron heat flux in ETG turbulence - Colyer, G; Schekochihin, A; Parra, F; Roach, C; Barnes, M; Ghim, Y; Dorland, W (IOP Publishing, 2017)
In electrostatic simulations of MAST plasma at electron-gyroradius scales, using the local flux-tube gyrokinetic code GS2 with adiabatic ions, we find that the long-time saturated electron heat flux (the level most relevant to energy transport) decreases as the electron collisionality decreases. At early simulation times, the heat flux "quasi-saturates" without any strong dependence on collisionality, and with the turbulence dominated by streamer-like radially elongated structures. However, the zonal fluctuation component continues to grow slowly until much later times, eventually leading to a new saturated state dominated by zonal modes and with the heat flux proportional to the collision rate, in approximate agreement with the experimentally observed collisionality scaling of the energy confinement in MAST. We outline an explanation of this effect based on a model of ETG turbulence dominated by zonal-nonzonal interactions and on an analytically derived scaling of the zonal-mode damping rate with the electron-ion collisionality. Improved energy confinement with decreasing collisionality is favourable towards the performance of future, hotter devices.